Bestrophin 2: An anion channel associated with neurogenesis in chemosensory systems - Klimmeck, Daniel; Daiber, Philipp; Frings, Stephan; Möhrlen, Frank (The journal of comparative neurology, 2009)
The chemosensory neuroepithelia of the vertebrate olfactory system share a life-long ability to regenerate. Novel neurons proliferate from basal stem cells that continuously replace old or damaged sensory neurons. The sensory neurons of the mouse and rat olfactory system specifically express bestrophin 2, a member of the bestrophin family of calcium-activated chloride channels. This channel was recently proposed to operate as a transduction channel in olfactory sensory cilia. We raised a polyclonal antibody against bestrophin 2 and characterized the expression pattern of this protein in the mouse main olfactory epithelium, septal organ of Masera, and vomeronasal organ. Comparison with the maturation markers growth-associated protein 43 and olfactory marker protein revealed that bestrophin 2 was expressed in developing sensory neurons of all chemosensory neuroepithelia, but was restricted to proximal cilia in mature sensory neurons. Our results suggest that bestrophin 2 plays a critical role during differentiation and growth of axons and cilia. In mature olfactory receptor neurons, it appears to support growth and function of sensory cilia. J. Comp. Neurol. 515:585-599, 2009. © 2009 Wiley-Liss, Inc.